Effect of information on reducing inappropriate expectations and requests for antibiotics - Thorpe, Alistair; Sirota, Miroslav; Orbell, Sheina; Juanchich, Marie (The British journal of psychology, 2021)
People often expect antibiotics when they are clinically inappropriate (e.g., for viral infections). This contributes significantly to physicians’ decisions to prescribe antibiotics when they are clinically inappropriate, causing harm to the individual and to society. In two pre‐registered studies employing UK general population samples (n1 = 402; n2 = 190), we evaluated the relationship between knowledge and beliefs with antibiotic expectations, and the effects of information provision on such expectations. We conducted a correlational study (study 1), in which we examined the role of antibiotic knowledge and beliefs and an experiment (study 2) in which we assessed the causal effect of information provision on antibiotic expectations. In study 1, we found that both knowledge and beliefs about antibiotics predicted antibiotic expectations. In study 2, a 2 (viral information: present vs. absent) × 2 (antibiotic information: present vs. absent) experimental between‐subjects design, information about antibiotic efficacy significantly reduced expectations for antibiotics, but viral aetiology information did not. Providing antibiotic information substantially diminishes inappropriate expectations of antibiotics. Health campaigns might also aim to change social attitudes and normative beliefs, since more complex sociocognitive processes underpin inappropriate expectations for antibiotics.